The tyranny of merit : what's become of the common good? - Sandel, Michael J. ([London] : Allen Lane, 2020)
"The world-renowned philosopher and author of the bestselling Justice explores the central question of our time: What has become of the common good? These are dangerous times for democracy. We live in an age of winners and losers, where the odds are stacked in favor of the already fortunate. Stalled social mobility and entrenched inequality give the lie to the American credo that "you can make it if you try". The consequence is a brew of anger and frustration that has fueled populist protest and extreme polarization, and led to deep distrust of both government and our fellow citizens--leaving us morally unprepared to face the profound challenges of our time. World-renowned philosopher Michael J. Sandel argues that to overcome the crises that are upending our world, we must rethink the attitudes toward success and failure that have accompanied globalization and rising inequality. Sandel shows the hubris a meritocracy generates among the winners and the harsh judgment it imposes on those left behind, and traces the dire consequences across a wide swath of American life. He offers an alternative way of thinking about success--more attentive to the role of luck in human affairs, more conducive to an ethic of humility and solidarity, and more affirming of the dignity of work. The Tyranny of Merit points us toward a hopeful vision of a new politics of the common good"-- Provided by publisher.
Prologue -- Introduction: Getting in -- Winners and losers -- "Great because good": a brief moral history of merit -- The rhetoric of rising -- Credentialism: the last acceptable prejudice -- Success ethics -- The sorting machine -- Recognizing work -- Conclusion: Merit and the common good.
Reprint. Originally published: New York : Farrar, Straus and Giroux, 2020.
Includes bibliographical references (p. 229-258) and index.
Keywords: Polarization (Social sciences) -- United States; Populism -- United States; Merit (Ethics) -- Social aspects -- United States; Public interest -- United States; Social mobility -- United States; Globalization -- Political aspects -- United States; United States -- Social conditions -- 21st century